Prognosis and distribution of ischemic stroke with negative diffusion-weighted imaging: a systematic review and meta-analysis - Alkhiri, Ahmed; Alturki, Fahad; Alansari, Nayef M.; Almaghrabi, Ahmed A.; Alghamdi, Basil A.; Alamri, Aser F.; Alghamdi, Saeed; Makkawi, Seraj (Frontiers in Neurology, 2024)
Background: Magnetic resonance diffusion-weighted imaging (DWI) is the most sensitive modality for ischemic stroke diagnosis. However, DWI may fail to detect ischemic lesions in a proportion of patients. Methods: Following PRISMA statement, a systematic search of Medline, Embase, and Web of Science was conducted until January 3, 2024. The inclusion was confined to English literature with sufficient reporting. Proportions of DWI-negative ischemic stroke were pooled. For binary variables, odds ratios (ORs) were computed using the random-effects model. Results: Fourteen studies constituting 16,268 patients with a clinical diagnosis of ischemic stroke and available DWI findings were included. Intravenous thrombolysis (IVT) was administered to 19.6% of the DWInegative group and 15.3% of the DWI-positive group. DWI-negative ischemic stroke was reported in 16% (95% CI: 10-24%; after sensitivity analysis: 11% [95% CI: 8-15%]) of stroke patients. Among minor stroke patients (National Institutes of Health Stroke scale [NIHSS] of 5 or less), 24% (95% CI 12-42%) had negative DWI findings. Predictors of DWI-negative scans included posterior circulation stroke, history of ischemic heart disease, prior stroke, or prior transient ischemic attack. Cardioembolic stroke (OR, 0.62, 95% CI: 0.41-0.93) and history of atrial fibrillation increased the likelihood of positive DWI findings (OR, 0.56, 95% CI: 0.45-0.71). Patients with DWI-negative ischemic stroke had higher odds of good functional outcomes (modified Rankin scale [mRS] of 0-1) (OR, 2.26; 95% CI: 1.03-4.92), lower odds of stroke recurrence (OR, 0.68; 95% CI: 0.48-0.96), and lower odds of severe disability or mortality (mRS of 3-6) (OR, 0.44; 95% CI: 0.34-0.57) compared to patients with positive DWI. Rates of symptomatic intracerebral hemorrhage after IVT were comparable between groups. Conclusions: DWI-negative findings were present in a significant proportion of ischemic stroke patients and may be utilized as a marker for favorable prognosis.